Burden of ageing spectrum of diseases in China, 1990–2021: a systematic analysis of global burden of disease study 2021 - Li Yang; Yuhan Xing; Xinjing Gao; Cui Guo; Dongze Wu (Frontiers in Public Health)
BackgroundPopulation aging represents a pressing challenge for China, given its vast population and the growing proportion of adults aged 65 years and older. The study aimed to assess burden of ageing spectrum of diseases in China from 1990 to 2021.MethodsThe main outcome measures were disability-adjusted life years (DALYs), summary exposure values (SEVs), and attributable risk. The average annual percent change (AAPC) in number and age specific rate (ASR) were calculated to quantify the temporal trends. The decomposition analysis was utilized to assess the impact of population aging on the burden of disease.ResultsFrom 1990 to 2021, The ASR of all-cause DALYs in China decreased by 35.94% overall and by 33.99% among individuals ≥65 years. However, the number of DALYs attributed to population ageing among people aged 65 and older has been increasing by 10.45 million. Chronic obstructive pulmonary disease, stroke, and ischemic heart disease are most significantly affected by the aging trend. Notably, the older adults population exhibited the most pronounced increase in HIV/AIDS-related DALYs, especially in the 70–74 years group (AAPC: 7.96, 95% CI 6.69, 9.24). Additionally, notable changes in COVID-19-related DALYs became evident beginning in 2019. Regarding risk factors, particulate matter pollution, smoking, and high sodium diets emerged as the top three contributors to health risks among the older adults.ConclusionTo address burden of ageing spectrum of diseases, China should leverage complementary roles of public and private insurance to manage cardiovascular and pulmonary disease, promote healthy environments and diets and prioritize prevention of HIV/AIDS.